2002
DOI: 10.1063/1.1458694
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activation studies of GaN implanted with Si from low to high dose

Abstract: Electrical activation studies of Si-implanted GaN grown on sapphire have been made as a function of ion dose and anneal temperature. Silicon was implanted at 200 keV with doses ranging from 1×1013 to 5×1015 cm−2 at room temperature. The samples were annealed from 1100 to 1350 °C with a 500-Å-thick AlN cap in a nitrogen environment. Samples implanted with high doses (⩾1×1015 cm−2) have optimum anneal temperatures of around 1350 °C, exhibiting a nearly 100% electrical activation efficiency, whereas low dose (⩽5×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…2 Ion implantation is a commonly utilized technique for the fabrication of semiconductor devices that are based on Si and GaAs materials. 7 It is also an important processing step that enables precisely controlled doping of nitride-based devices. Ion implantation with various ions, doses, and energies is used for the fabrication of the channel layer in transistors, creating highly conductive n-type regions for improving access resistance, and for device isolation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Ion implantation is a commonly utilized technique for the fabrication of semiconductor devices that are based on Si and GaAs materials. 7 It is also an important processing step that enables precisely controlled doping of nitride-based devices. Ion implantation with various ions, doses, and energies is used for the fabrication of the channel layer in transistors, creating highly conductive n-type regions for improving access resistance, and for device isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Surface damage can be avoided to some extent by using a proximity cap during annealing, as discussed by Fellows et al 7 In Fig. 4 we compare the surfaces of one piece of sample 474ia with another treated in the same way but with an AlN proximity cap in position during annealing.…”
mentioning
confidence: 95%
“…However, some localized failures of the AlN caps are observed; several groups have reported pitted surfaces in Siimplanted AlN capped GaN after annealing at temperatures higher than or equal to 1300°C. 3,[7][8][9] The structure of these pits and the mechanism that leads to their formation has not been fully explained. In this letter, we present the microscopic study of the failure mechanisms of such caps in relation to the protection that they provide during high temperature annealing of RE implanted GaN epilayers providing clear indications for producing caps with a higher resistance to degradation.…”
mentioning
confidence: 99%
“…Previous studies of ion-implanted III-nitride materials [3,4] have shown that the activation of implanted impurities is much more difficult than for conventional compound semiconductors such as GaAs and InP. Recently, Fellows et al [5] reported a 100% electrical activation for Si-implanted GaN with high doses (≥1 × 10 15 cm…”
mentioning
confidence: 97%